Predictive value of WBC differential on different clinical variables& scAR formation in Chickenpox (variceila) - M Al-Kumait, Thikraa; A. Abd, saifeldeen; D' Moohy Alosy, Baha (Tikrit Journal of Pharmaceutical Sciences, 2023)
This prospective study was executed over a period of 5 year from February 2003 to December 2007 in the central pediatric hospital & 5 primary health care center in Baghdad then in the Tikrit hospital & trvo private clinic in Tikrit, one handered trventy (120) children lvith chickenpox were enrolled in this study' By 95% cl Pairecl sanrples Test effect oi wBC courlt on different clinical variables & scAR formation' The result indicate that Rash usual site lvas commonest & safest type of milder disease (l15 =%96)while Rash unusual site give us pointer to predict the moderate course of disease &it rvas documented for first time in our study only, Hyper pigmented area can be safest type of discoloration happcned in course of diseasc .llcmorrhagic Rash0.2g7 gives predictive indicator for serious type of aggrcssivc picturc of chickenpox